Control of intestinal inflammation by glycosylation-dependent lectin-driven immunoregulatory circuits - Morosi, Luciano Gastón (2021)
Diverse immunoregulatory circuits operate to preserve intestinal homeostasis and prevent inflammation. Galectin-1 (Gal1), a β-galactoside-binding protein, promotes homeostasis by reprogramming innate and adaptive immunity. Here, we identify a glycosylation-dependent "on-off"circuit driven by Gal1 and its glycosylated ligands that controls intestinal immunopathology by targeting activated CD8+ T cells and shaping the cytokine profile. In patients with inflammatory bowel disease (IBD), augmented Gal1 was associated with dysregulated expression of core 2 β6-N-acetylglucosaminyltransferase 1 (C2GNT1) and α(2,6)-sialyltransferase 1 (ST6GAL1), glycosyltransferases responsible for creating or masking Gal1 ligands. Mice lacking Gal1 exhibited exacerbated colitis and augmented mucosal CD8+ T cell activation in response to 2,4,6-trinitrobenzenesulfonic acid; this phenotype was partially ameliorated by treatment with recombinant Gal1. While C2gnt1-/- mice exhibited aggravated colitis, St6gal1-/- mice showed attenuated inflammation. These effects were associated with intrinsic T cell glycosylation. Thus, Gal1 and its glycosylated ligands act to preserve intestinal homeostasis by recalibrating T cell immunity.